NEOADJUVANT TREATMENT IN RECTAL CANCER - Youssef EL MARRAK (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2021)
Background: Neoadjuvant treatment is a pillar of the current standard care of locally advanced rectal cancer. Many approaches are used as neoadjuvant treatment, while more are analyzed and studied to further improve the current ones. Aim: To investigate the neoadjuvant treatment as a current standard of care for locally advanced rectal cancer Methods: A review of the literature was performed to investigate and evaluate the neoadjuvant treatment in the current standard of care for locally advanced rectal cancer. The review includes original articles published in English, included and not limited to systematic reviews, prospective studies, and retrospective ones. It also included chapters and data from different books and scientific sites. Results: Short-course radiotherapy and long-course chemoradiotherapy have comparable results, while total neoadjuvant treatment seems like a promising approach, although more studies are needed. Moreover, intensified neoadjuvant treatment's results differ depending on the strategy used, and they show new directions for a better treatment approach. Conclusion: Neoadjuvant treatment shows clearly its advantages in treating locally advanced rectal cancer, especially when it comes to improving local control and increasing pathological complete response
Keywords: Rectal cancer; Neoadjuvant treatment; Radiotherapy; Chemotherapy